Improving student engagement and behavioural outcomes via persistence among distance learners - Norizan Baba Rahim, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Student engagement assists distance learners gain specific skills and to realise the worth of their rewarding educational experience. However, if persistence is not adequately present, the distance learners might quit an online course. Thus, this study aimed to investigate the relationship between online student engagement towards student satisfaction and learning outcomes and to examine the moderating effect of persistence between online student engagement towards student satisfaction and learning outcomes. The research model was tested upon engagement theory as an underlying theory to support the research framework. Purposive sampling technique was used to collect data via online survey questionnaires for three weeks. The research hypotheses are examined through correlation and path analysis of 321 distance learners from one of the public universities in Malaysia using Partial Least Square (PLS) 3.0. Results of analysis demonstrated that persistence was found to moderate the relationship between online student engagement towards student satisfaction and learning outcomes. This finding implies that distance learners who commit themselves to a goal will highly likely persist, and the more courses a student finishes, the closer he or she will be to graduating. Based on the results, this research suggests the management of Malaysian distance education institutions to create rapport between online programme staff and distance learners at an early stage. Additionally, online programmes must promote and establish support networks for distance learners to resolve personal or professional difficulties in improving retention and preventing them from dropping out of online programmes.